The Influence of Job Stress, Job Satisfaction & Organizational Commitment Towards Turnover Intention for Millennials and Generation Z Employees in Internet Companies in Indonesia - Yosef Budiman; Pauline H. Pattyranie Tan (Jurnal Mantik, 2022)
Internet companies managed to become industry of choice of younger generations to work. Nevertheless, the industry faced challenges in terms of managing people, which is soaring high turnover rate. This problem, apart from costly for the organization, might harm organization's overall performance. Research is performed to identify if job stress that is presumed to be high among Millennials and Generation Z significantly influence turnover intention and other HR metrics such as job satisfaction and organizational commitment. While, explain if other factors might be having more influence to turnover intention. This research collects data from 103 respondents across job function, gender, tenure within the organization and marital status. The respondents are all working for internet companies in Indonesia, and below 40 years old of age (to be considered millennials and generation Z). Data analysis is performed using Partial Least Square - Structural Equation Modelling (PLS-SEM). Based on the hypothesis testing, it is concluded that there is significant influence between job stress towards job satisfaction and organizational commitment (which can be problematic for the organization). In addition, organizational commitment has significant influence towards turnover intention of these group of employees.